Performance, Body Temperature and Egg Quality of Laying Hens Fed Vitamins D and C Under Three Environmental Temperatures - Faria,DE (2001)
Three experiments were conducted in a climatic chamber to determine the effects of vitamins D3 and C supplementation on performance, body temperature, and egg quality under thermoneutral temperature (24.8º to 27.0º C), a cyclic heat stress (26.2º C for 16 h and 32.1º C for 8 h) and a constant heat stress (30.0º to 32.0º C) for three weeks in each temperature. One hundred forty-four White Leghorn hens aged 31 weeks were used in a completely randomized design with a factorial arrangement of 3 x 3: vitamin D3 (2,500, 3,000, and 3,500 IU/kg) and vitamin C (0, 200, and 400 ppm), with a total of nine treatments with four replicates of four hens each. Parameters measured included feed intake (FI), feed:gain (FG), egg production (EP), egg weight (EW), egg mass (EM), rectal (RT) and dorsal temperatures (DT), percentages of albumen (AP) and yolk (YP), Haugh units (HU), yolk index (YI), shell percent (SP), shell thickness (ST) and egg specific gravity (ESG). Vitamin D3 influenced the parameters SP, ST, ESG and DT; vitamin C influenced YI, SP and ESG. There was no influence of environmental temperature only on HU. It was concluded that higher levels of vitamin D3 and 200 or 400 ppm of vitamin C can be improve eggshell quality and that heat stress impaired the main characteristics evaluated.